Dampak Program Simantri 245 Banteng Rene terhadap Subak Renon di Kecamatan Denpasar Selatan, Denpasar - JAYA, AHMAD SURYA; WINDIA, I WAYAN; PARINING, NYOMAN (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2017)
Impact of 245 Rene Bull Simantri Program on Subak Renon in South Denpasar District, Denpasar Simantri is one of the strategies in order to accelerate the adoption of agricultural technology by integrating the agricultural sector into supporting sectors in accordance with the potential of each region. The purpose of this study was to analyze and describe the impact of 245 Rene Bull Simantri program on Subak Renon Renon. The choice of research location was made on purpose with consideration that the Subak location was within the urban areas. The existence of Simantri program in in Subak did not run well. Subak Renon which are adjacent to several other Simantri already capable of utilizing livestock waste into fertilizer. The 30 samples were taken out of 102 members of Subak, using a sampling technique of random sampling. The data were collected through interviews, observation and documentation. The data analysis used descriptive methods. The results showed that there was no impact of 245 Simantri program on Subak Renon in terms of increased cropping intensity, the institutional development supporting agricultural activities, the increase of farmers' income, the area of organic lands, the creation and the development of organic agriculture and infrastructure in the region of Subak Renon, so that the activities of 245 Rene Bull Simantri Renon were inactivated. The suggestion that can be made by the writer associated with this study is that the government is expected to reactivate back 245 Rene Bull Simantri in Renon and the provincial and municipal governments are expected to provide competent assistance counselors and fund assistance in order to give a positive impact on Subak Renon.
Keywords: simantri; impact; agricultural activities; organic agriculture